Bag Valve Mask with Ventilation Indicator (BVM-VI) prototype for ventilation rhythm in Basic Life Support - Pratama Yulianto; Endang Triyanto; Ridlwan Kamaluddin; Adhe Akbar Azanni (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Bag valve mask (BVM) are a practical choice for emergency medical personnel to treat out-of-hospital cardiac arrest (OHCA). However, the use of currently available conventional BVM still often results in overventilation in cases of cardiac arrest or respiratory failure. Globally, 79% of hyperventilation events occur during Basic Life Support (BLS) with BVM. This study aims to produce a prototype BVM-VI. Method The prototyping method of Research and Development design was chosen as the primary method, followed by black box testing with clinical, practical, and academic experts, and ended with limited scale testing with 10 users. Result BVM-VI is the result of combining conventional BVM with a portable indicator light module to signal ventilation actions. Expert assessment using the black box test method with CVI analysis resulted in a content validity score of 100%. A limited study conducted by nursing students using a survey method showed reliability with an Intraclass Correlation Coefficient (ICC) of 0.769. Conclusion BVM-VI became the initial prototype for developing a ventilation aid with breathing rhythm adjustment in BLS.